TRANSFORMASI KOMUNIKASI INTERNAL DALAM UPAYA MENINGKATKAN SEMANGAT KERJA APARATUR PEMERINTAH DESA SUKAMULYA - Rachmat Rachmat; Zaini Uzlah; Ahmad Wahyudi (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the effect of internal communication of the village head on the work motivation of village officials in Sukamulya Village, Warungkondang District, Cianjur Regency. The background of this research is the presence of information distortion, lack of routine communication forums, and low work discipline that hinder organizational effectiveness at the village level. The research method used is a quantitative approach with an explanatory research design. Data were collected through questionnaires from 35 respondents using a saturated sampling technique and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 3. The results show that internal communication has a positive and significant effect on work motivation, with a path coefficient of 0.825. Statistically, the t-statistic value of 2.430 (>1.96) and p-value of 0.015 (<0.05) confirm that improvements in internal communication quality directly enhance work motivation. The R-square value of 0.680 indicates that internal communication explains 68% of the variance in work motivation. Additionally, the model demonstrates moderate predictive relevance with a Q-square value of 0.278. These findings highlight the importance of transparency, feedback systems, and efficient information flow in fostering motivation and professionalism among village officials.